Free-standing and binder-free highly N-doped carbon/sulfur cathodes with tailorable loading for high-areal-capacity lithium–sulfur batteries. Issue 41 (30th September 2015) - Schneider, A.; Suchomski, C.; Sommer, H.; Janek, J.; Brezesinski, T.
Abstract : A practical high-loading Li–S battery is realized by using free-standing and highly conductive N-doped carbon paper as sulfur host. Abstract : A facile hard-templating method has been developed to prepare highly N-doped carbon/sulfur cathodes with thickness < 200 μm and large areal mass loading (>2.5 mgsulfur cm −2 ). Lithium–sulfur batteries using this free-standing and binder-free hierarchical hybrid design exhibit good cycling performance, with stable areal capacities of 3.0 mA h cm −2, owing to favorable properties of the carbon host.